Agminated Fibroblastic Conective Tissue Nevus: A New Clinical Presentation. Issue 4 (14th June 2016) - Downey, Camila; Requena, Luis; Bagué, Silvia; Sánchez Martínez, Miquel Ángel; Lloreta, Josep; Baselga, Eulalia
Abstract: Connective tissue nevi are benign hamartomatous lesions in which one or several of the components of the dermis (collagen, elastin, glicosaminoglycans) show predominance or depletion. Recently, de Feraudy et al broadened the spectrum of connective tissue nevus, describing fibroblastic connective tissue nevus (FCTN), which is characterized by proliferation of CD34 + cells of fibroblastic and myofibroblastic lineage. Only solitary papules and nodules have been described. We present the first case of FCTN with multiple agminated lesions on the leg of an infant and the difficulties encountered in the differential diagnosis with dermatofibrosarcoma protuberans.